Purwa Rupa Sistem Pengaman Sepeda Motor Berbasis IoT (Internet of Things - Juwariyah, Tatik; Widiyanto, Didit; Sulasmingsih, Sri (Jurnal Otomasi Kontrol dan Instrumentasi, 2019)
The case of motorbike theft is one of the common problems in the community that needs to be found a solution. One  of solutions  to  secure  motorbikes  from  potential  theft  is  to install smart vehicle technology (smart vehicl e). This paper describes  the  design  of  IoT  vehicle  safety  systems  using Arduino  Mega  microcontroller,  fingerprint  sensor, ESP8266 and  Blynk applications on smartphones. For the experiment,  this  study  uses  an  automatic  transmission motorbike that represents the public motorcycle model. For research  methods,  this  study  uses  three  stages  of  design. The  first  stage  is to  compile  the  prototype  hardware  of  a motorcycle security system using a fingerprint sensor, and a  microcontroller.  The  second  phase,  IoT  that  uses  a notification  system  on  ESP8266-based  smartphones  and Blynk  applications  are  designed.  In  the  third  stage,  the security  system  and  notification  system  sent  via  the smartphone are combined. In the results of the first phase of the trial, five people (whose fingerprints were registered and not registered) were involved to show the system was working as we expected. This means that even if the vehicle ignition  is  in  the  "ON"  position,  the  motorcycle  engine cannot be started using an electric starter method or using a  crank  start  system.  To  be  able  to  "start"  a  motorcycle engine, the user's fingerprint must be verified first. In the second  phase  of  the  trial,  notification  via  the  Blynk application  on  the  smartphone  will  show  someone's fingerprint that started the motorcycle has been verified or not  verified.  Finally  in  the  final  stage  of  the  trial, information  systems  in  the  form  of  notifications  on smartphones can be realized to inform users who are trying to  start  the  motorcycle  engine  have  been  verified  or  not verified. The  results  of  this  study  are  expected  to  become IoT  applied  references  for  motorcycle  and  other  vehicle security systems